Increased insensible water loss in newborn infants nursed under radiant heaters. Issue 6048 (4th December 1976) - Jones, R W; Rochefort, M J; Baum, J D
Abstract : Urine osmolality was studied in 38 babies nursed in conventional incubators or cots and 18 nursed under an overhead radiant heat shield. Among 50 babies receiving a similar fluid intake in the first 48 hours of life mean urinary osmolality was significantly higher in the radiant heater group. In babies weighing less than 1500 g a trend towards higher urinary osmolalities was recorded in those nursed under radiant heaters even though they had received amost double the fluid intake of the incubator group. Severe hypernatraemia occurred in four of the five babies weighing less than 1000 g who were nursed under radiant heaters but in none of the seven babies of similar birth weight nursed in incubators. These findings are consistent with previous observations of an increase in insensible water loss in babies nursed under radiant heaters and emphasise the importance of providing enough extra water for these infants and the need for close monitoring of their fluid balance. The latter may be done at the bedside by measuring urinary specific gravity with a hand refractometer.